Analysis Of The Psychological Aspects Of Pencak Silat Athletes Who Undergo Rapid Weight Loss And Its Impact On Competition Performance - Faisal Hanif Mico Satriaji; Sahri (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Observations from the 2025 Semarang City Championship indicate that pencak silat athletes rely on Rapid Weight Loss (RWL), which triggers psychological stress, mental turmoil, and emotional instability. The consequences include impaired focus and premature fatigue. This study aims to analyze the influence of the affective, cognitive, and conative psychological aspects of athletes who practice RWL on their competition performance to address mental management challenges during competition. The research design used in this study is quantitative descriptive research. The population in this study consists of pencak silat athletes from the Dragon Fighter Club, with a sample size of 12 athletes. The instrument used in this study was a questionnaire. This questionnaire presented statements regarding psychological aspects such as affective (emotional), cognitive (focus and self-confidence), and conative (motivation and mental fatigue). Findings regarding the affective aspect indicate that athletes agreed with the variables of mood (r=2.5) and self-confidence (r=2.91), but disagreed regarding emotional control (r=2.33) and response to provocation (r=2.25). Cognitively, athletes agreed on focus (r=2.67) and reaction time (r=2.58), but disagreed regarding concentration (r=1.83) and memory (r=2.5). The conative aspect showed strong agreement regarding discipline (r=3.33), enthusiasm (r=3.83), and perseverance (r=3.5), though athletes disagreed regarding motivation (r=2). The analysis concluded that the affective aspect of pencak silat athletes was emotionally impacted in the mood dimension due to rapid weight loss. Cognitively, athletes experienced slower reaction times and reduced response speed during competition. However, the conative aspect showed no significant impact on motivation and mental fatigue. A limitation of this study is the lack of specific prior research, so the results remain subjective.